2015
DOI: 10.1002/asna.201412137
|View full text |Cite
|
Sign up to set email alerts
|

Classical Cepheids in the Galactic outer ring R1R2

Abstract: The kinematics and distribution of classical Cepheids within ∼ 3 kpc from the Sun suggest the existence of the outer ring R1R ′ 2 in the Galaxy. The optimum value of the solar position angle with respect to the major axis of the bar, θ b , providing the best agreement between the distribution of Cepheids and model particles is θ b = 37 ± 13• . The kinematical features obtained for Cepheids with negative Galactocentric radial velocity VR are consistent with the solar location near the descending segment of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 81 publications
5
46
1
Order By: Relevance
“…We found that extinction A V toward open clusters grows most rapidly in the direction of the Galactic center (l = 315-360 • and 0-45 • ) and in the sector 45-90 • , while it is minimal in the direction of the the Carina complex 270-315 • and the anticenter 225-270 • . Note that we found similar features in the variations of extinction for classical Cepheids (Mel'nik et al 2015). Possibly, the sharp growth of extinction can be attributed to the presence of the Galactic outer ring R 1 at the heliocentric distance 1-2 kpc in the direction to the Galactic center.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…We found that extinction A V toward open clusters grows most rapidly in the direction of the Galactic center (l = 315-360 • and 0-45 • ) and in the sector 45-90 • , while it is minimal in the direction of the the Carina complex 270-315 • and the anticenter 225-270 • . Note that we found similar features in the variations of extinction for classical Cepheids (Mel'nik et al 2015). Possibly, the sharp growth of extinction can be attributed to the presence of the Galactic outer ring R 1 at the heliocentric distance 1-2 kpc in the direction to the Galactic center.…”
Section: Discussionsupporting
confidence: 80%
“…V . Note that we found similar features in variations of extinction for classical Cepheids (Mel'nik et al 2015). Both groups of young objects, open clusters and Cepheids, show a sharp growth of extinction in the direction toward the Galactic center (see also Neckel & Klare 1980;Marshall et al 2006).…”
Section: Surface Density and Extinction In Different Sectorssupporting
confidence: 78%
See 3 more Smart Citations